Single barometer : the analysis effect of value based measure of performance towards stock price evidence from Malaysia companies listed in Bursa Malaysia / Muhammad Rey Zairan - Zairan, Muhammad Rey (2016)
The traditional measure of performance such as Earning per share and Return on equity was widely used around the world to measure stockholder value creation but due to its weakness, the value based measures was created. Nowadays, most investor more prefer to use value based measure of performance which focuses on changes in value. Value based measure consist of 2 components: Economic Value Added (EVA) and Market Value Added (MVA). In this study, EVA obtained its value from difference between return and cost. MVA is the present value of future EVA. Secondary data was collected from the company's financial reports and Bursa Malaysia. This study involved 30 companies in the Malaysia stock market from 3 different industries during as well as pre, during event and post event of the Global financial crisis (2004-2012). A panel data analysis as an analytical method was conducted to show whether EVA and MVA had a strong relationship with stock price. The Fixed Effect Model, Random Effect Model and Ordinary Least Square (OLS) test was performed and Fixed Effect Model Accepted. It was found that only MVA had a significant relationship with Stock price at 99% critical level.